Model Collaborative Governance dalam Pengelolaan Program Ekonomi Mikro di Desa Waeheru Kecamatan Baguala Kota Ambon - Kotaromalos, Amir Faisal; Tuhumury, Joana Joanita; Latuconsina, Nurainy (Jurnal Ilmiah Global Education, 2024)
The approach taken in doing this research is both quantitative and qualitative. Using Simple Likert Scale Formulas - and Qualitative Approaches: Interactive Analysis Models by Miles and Huberman (2014). The results obtained from this study are indicators (1). Being in a very bad category, because the average rating of the Governance Collaboration Implementation Indicator is in this category (1,56), where the sub-indicator Face to face to Dialogue is in very poor condition (1,54) The sub-Indicator Trust Building is also very poor (1,48), - Commitment to the Process, very poor (1,65). Shared Understanding, very bad (1,47) and Intermediate Outcomes are very bad. (1,68). Indicators (2) Collaboration inhibitors of governance, low knowledge factors, the spirit of entrepreneurship and self-reliance of low-level societies, awareness factors of unformed parties, personal ego and institutional factors of high-level Parties, budgetary factors that are still low. Indicators (3) The role and function of Micro Enterprise Building by Cooperative Services as a role and elements of Bank Indonesia as a Commodity/Product/Type Enterprise Builder (KPJU), the role of expanding access or financial inclusion by OJK, Capacity Building Micro Enterprises by Colleges, Motivation and Business Examples of Successful Entrepreneurs.